2016
DOI: 10.1097/iae.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Morphologic Outcomes of Intravitreal Ranibizumab for Diabetic Macular Edema Based on Optical Coherence Tomography Patterns

Abstract: Vision gains and retinal anatomy improvement were maintained in all three types during the first year of IVR administration. Especially, DRT maintained a good response to ranibizumab in a fewer number of injections. Disruption of the photoreceptor integrity at the baseline was correlated with poorer visual outcome and occurred more frequently in SRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
106
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 21 publications
9
106
3
1
Order By: Relevance
“…A study by Reznicek et al 37 showed that in patients being treated with RBZ the IS-OS layer defect actually improved; with previous animal models suggesting the possibility of remodelling or regeneration of the photoreceptor layer, it is interesting to suggest that OCT disruptions in this layer are not static but fluid in response to treatment. Two recent studies by Seo et al 38 and Kang et al 39 showed similar regenerative effects of the IS-OS and ELM layer in all subtypes of oedema—cystoid, SRF, and diffuse.…”
Section: Defining Responsementioning
confidence: 69%
“…A study by Reznicek et al 37 showed that in patients being treated with RBZ the IS-OS layer defect actually improved; with previous animal models suggesting the possibility of remodelling or regeneration of the photoreceptor layer, it is interesting to suggest that OCT disruptions in this layer are not static but fluid in response to treatment. Two recent studies by Seo et al 38 and Kang et al 39 showed similar regenerative effects of the IS-OS and ELM layer in all subtypes of oedema—cystoid, SRF, and diffuse.…”
Section: Defining Responsementioning
confidence: 69%
“…A few studies have shown these biomarkers of the photoreceptor status as predictors of visual outcomes after anti-VEGF therapy313233. However, the effects of anti-VEGF therapy on photoreceptor damage are controversial343536.…”
mentioning
confidence: 99%
“…The absence of limiting boundaries creates a particular pattern region commonly designed by ophthalmologists as a "sponge-like" appearance [65], as represented in Figure 2.20. As a result, the thickness of the lower retina region increases, which consequently leads to an increment of the entire normal retinal thickness, modifying significantly the normal morphology and tissue patterns.…”
Section: Diffuse Retinal Thickening -Drtmentioning
confidence: 99%
“…Typically, the SRD type is characterized by a dome shape at the inferior retinal layers whereas the CME type is defined by the presence of the intraretinal cystoid spaces of low reflectivity separated by highly reflective boundaries that represent the intraretinal cystoid-like cavities [48]. Finally, the DRT type is commonly characterized as a "sponge-like" swelling appearance as a result of a regional fluid spread with reduced intraretinal reflectivity [7,65]. Despite the fact that these three types derive from the same cause, the leak of fluid, their characteristics and visual appearance within the retinal layers are enormously different, as described in detail in the sections: SRD in section 2.4.1, CME in section 2.4.2 and, finally, the CME in section 2.4.3.…”
Section: Macular Edema Typesmentioning
confidence: 99%